2008
DOI: 10.1074/jbc.m708230200
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Suppressor Mutation of the met30 Cell Cycle Defect Suggests Regulation of the Saccharomyces cerevisiae Met4-Cbf1 Transcription Complex by Met32

Abstract: Met30 is the substrate recognition subunit of the essential ubiquitin ligase SCF Met30 . The essential function of Met30 is the inactivation of the Saccharomyces cerevisiae transcription factor Met4, because fully activated Met4 induces a cell cycle arrest. Met4 regulates expression of genes involved in the sulfur assimilation pathway and coordinates the transcriptional program and cell cycle progression in response to cadmium and arsenic stress. Met4 lacks DNA binding activity and requires either Cbf1 or one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Consistent with our analysis, met32 strains have decreased fitness under sulfate limitation, whereas met31 strains do not (Payen et al 2015). Our data also strengthen the observation that Met31 and Met32 are not fully redundant (Su et al 2008;Cormier et al 2010). Because each binding site in the SUL1 promoter is at least one mismatch away from its consensus site, their annotation by sequence-based motif-finding methods is difficult.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with our analysis, met32 strains have decreased fitness under sulfate limitation, whereas met31 strains do not (Payen et al 2015). Our data also strengthen the observation that Met31 and Met32 are not fully redundant (Su et al 2008;Cormier et al 2010). Because each binding site in the SUL1 promoter is at least one mismatch away from its consensus site, their annotation by sequence-based motif-finding methods is difficult.…”
Section: Discussionsupporting
confidence: 57%
“…It has previously been demonstrated that Met4 is a substrate for SCF Met30 and a Met30/Met4 complex can be detected in vivo (Kaiser et al, 2000; Rouillon et al, 2000). In addition, Met4 interacts with its co-factor Met32 in vivo and in vitro (Blaiseau and Thomas, 1998; Su et al, 2008), and it was therefore possible that the Met30/Met32 interaction we detected was indirect through the mutual binding partner Met4. Indeed, no interaction between Met30 and Met32 could be detected in met4 Δ mutants, suggesting that Met4 mediates the Met30/Met32 interaction (Figure 2A).…”
Section: Resultsmentioning
confidence: 98%
“…Consistent with Met32 having an important role in MET gene expression, a truncated version of Met32 (Met32D145-192) acts as a dominant suppressor of met30 null mutations by interfering with the recruitment of Met4 to both Cbf1 and Met31/32-dependent promoters (Su et al 2008).…”
Section: Pathway Genesmentioning
confidence: 99%